Are there different types of dieters? A review of personality and dietary restraint. (1st June 2018) - Mills, Jennifer S.; Weinheimer, Laura; Polivy, Janet; Herman, C. Peter
Abstract: We review the research on the association between personality and dietary restraint as measured by commonly-used self-report assessment instruments (Restraint Scale, TFEQ, DEBQ, and EDE-Q). In order to expand our understanding of the potentially different types of dieters, we examine the different personality profiles that emerge from existing studies of restraint and personality, including associations between restraint and body dissatisfaction and body focus, self-esteem, neuroticism, sensation seeking, impulsivity, perfectionism and narcissism. This research provides some preliminary evidence that different measures of restraint are associated not only with different eating behaviours, but that they capture different personality profiles.